Organic chemistry - Klein, David R. (John Wiley & Sons, 2018)
Klein's Organic Chemistry, Global Edition is not merely a compilation of principles, but rather, it is a disciplined method of thought and analysis. This book employs a skills-based approach to bridge the gap between theory and practice. It provides extensive coverage of the principles and helps students become proficient at approaching new situations methodically based on a repertoire of skills.